Kompetensi Dokter Umum di Unit Gawat Darurat dalam Manajemen Jalan Napas: Tinjauan Sistematis dan Meta-Analisis (2015–2025) - Paramartha, I Kadek Adi; Made Paramartha Kesuma (Jurnal Medicare, 2025)
Emergency airway management is frequently performed by general practitioners in emergency departments (EDs); however, their success rates remain poorly defined. We conducted a systematic review and meta-analysis of PubMed, MEDLINE, and Google Scholar (2015–2025) for studies reporting endotracheal intubation (ETI) or supraglottic airway (SGA) placement by general practitioners or non-specialist residents in the ED. Exclusion criteria were specialist operators and surgical airway procedures. Fifteen studies (31 874 ETI attempts) were analysed qualitatively; five sufficiently homogeneous studies were pooled in a random-effects meta-analysis using first-pass success (FPS) as the effect measure. The pooled FPS for general practitioners was 75 % (95 % CI, 70–80 %; I² = 92 %). Major complications (hypoxaemia, hypotension, aspiration) ranged from 12 % to 49 % and increased significantly with each additional intubation attempt. Simulation studies showed 97 % successful ventilation with SGA placement by novice operators compared with 62 % with ETI. Determinants of success included ≥ 50 prior ETI experiences, use of rapid sequence intubation, video laryngoscopy, senior supervision, adherence to difficult-airway algorithms, and regular simulation training. ETI competency among general practitioners in EDs remains below the international benchmark of ≥ 85 % FPS. Enhanced formal training, wider availability of video laryngoscopes and SGAs, structured supervision protocols, and recurring simulation programmes are recommended to close this skills gap and improve patient safety.